2021
DOI: 10.4062/biomolther.2021.037
|View full text |Cite
|
Sign up to set email alerts
|

Change in Cationic Amino Acid Transport System and Effect of Lysine Pretreatment on Inflammatory State in Amyotrophic Lateral Sclerosis Cell Model

Abstract: Amyotrophic lateral sclerosis (ALS) is a lethal neurological disorder characterized by the deterioration of motor neurons. The aim of this study was to investigate alteration of cationic amino acid transporter (CAT-1) activity in the transport of lysine and the pretreatment effect of lysine on pro-inflammatory states in an amyotrophic lateral sclerosis cell line. The mRNA expression of cationic amino acid transporter 1 was lower in NSC-34/hSOD1 G93A (MT) than the control cell line (WT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Arginine is known to be transported by major four cationic amino acid transporters including system y + , b 0,+ , B 0,+ , and y + L. Previous studies have also shown that system y + is an arginine-specific transporter associated with several cell types, including neurons [ 30 , 36 , 37 , 38 ]. In our differential analysis ( Table 3 ), we found that system y + is primarily involved in arginine transport, and Slc7a1 is expressed in NSC-34 cell lines, as shown in our previous work [ 39 ]. Furthermore, our results suggest that system b 0,+ is involved, to a lesser extent, in L-arginine transport in MT and WT cell lines, although mRNA expression has not been observed in NSC-34 cell lines [ 39 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Arginine is known to be transported by major four cationic amino acid transporters including system y + , b 0,+ , B 0,+ , and y + L. Previous studies have also shown that system y + is an arginine-specific transporter associated with several cell types, including neurons [ 30 , 36 , 37 , 38 ]. In our differential analysis ( Table 3 ), we found that system y + is primarily involved in arginine transport, and Slc7a1 is expressed in NSC-34 cell lines, as shown in our previous work [ 39 ]. Furthermore, our results suggest that system b 0,+ is involved, to a lesser extent, in L-arginine transport in MT and WT cell lines, although mRNA expression has not been observed in NSC-34 cell lines [ 39 ].…”
Section: Discussionsupporting
confidence: 83%
“…In our differential analysis ( Table 3 ), we found that system y + is primarily involved in arginine transport, and Slc7a1 is expressed in NSC-34 cell lines, as shown in our previous work [ 39 ]. Furthermore, our results suggest that system b 0,+ is involved, to a lesser extent, in L-arginine transport in MT and WT cell lines, although mRNA expression has not been observed in NSC-34 cell lines [ 39 ]. Earlier studies have showed L-arginine transport by both systems y + L and y + in human umbilical vein endothelial cells [ 40 ]; and in the uptake of arginine in the CAD cells [ 30 ], however, our data showed no involvement of system y + L in the MT cell lines, whereas only 3.4% involvement was observed in the WT cell lines.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our research work, we have compared the MT cell line with the WT cell line and together referred to them as ALS model cell lines. The procedure for the uptake in NSC-34 cells has been described in earlier studies [ 24 , 25 ]. Another cell model used in our previous research work is a BBB in vitro model.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on N-methyl-D-aspartate receptors, paeonol was shown to provide protection to neurons of the rat hippocampus against injury induced by the withdrawal of oxygen and glucose [ 17 ]. Our previous research showed the altered transport of various amino acids, for instance, citrulline, lysine, tryptophan, and acidic drugs, including 4-phenylbutyric acid and valproic acid [ 18 ], as well as the energy-metabolizing compound carnitine in an ALS model cell line [ 19 , 20 , 21 , 22 , 23 ]. Since paeonol had a neuroprotective effect on activated microglial cells and hippocampal neurons, we assumed that studying the transport of paeonol in NSC-34 cell lines would bring new insights into its role in ALS.…”
Section: Introductionmentioning
confidence: 99%